INFLUÊNCIA DA GEOMETRIA E ARBORIZAÇÃO NO ESTRESSE TÉRMICO DE PEDESTRES EM CENÁRIOS DE CÂNIONS URBANOS DE UMUARAMA PR - Lima, Diana Carla Rodrigues; Lima, Pollyanna Rodrigues; Caram, Rosana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The quality of urban spaces depends on the adaptation of urban designs to their climatic context. In Brazil, the master plan is the instrument of municipal governments responsible for regulating urban design. The city of Umuarama in the state of Paraná recently approved a new Master Plan and is developing an Urban Tree Plan. The objective of this research is to verify the influence of urban geometry and tree plan on the thermal stress of pedestrians in urban canyon scenarios in Umuarama, based on microclimate models generated with Envi-MET software. The Physiological Equivalent Temperature (PET) index was used to evaluate the thermal stress. The results showed that the PET tends to be lower in deeper urban canyons with greater green space coverage. Furthermore, this study demonstrated the benefits of computational simulation in the development of municipal plans for the production of climateoriented urban designs.